Impact of COVID 19 on Global Supply Chains and the Asian Shipping and Port Sector: An Operations Perspective. - Oloruntoba, Richard (2020)
The paper discusses the general impacts of COVID-19 and attendant response measures on global supply chains, and the operational aspects of the Asian shipping and ports sector. The paper then delves into the effects of global developments before and after COVID-19 on Asian shipping and ports industry, and suggests operational areas that shipping companies, ports, and shippers in Asia may need to pay attention to, going forward, in order to forestall further pandemic-related losses and risks.